The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s1806-66902014000100023
|View full text |Cite
|
Sign up to set email alerts
|

Persistência e liberação de elementos da fitomassa do consórcio crotalária com milheto sob fragmentação

Abstract: RESUMO -Objetivou-se, com esse trabalho, avaliar a taxa de decomposição e a velocidade de liberação de macronutrientes e Si da fitomassa do consórcio crotalária mais milheto, em função do tempo após manejo, sem e com fragmentação. O experimento foi conduzido em condições de campo, em Botucatu-SP. O delineamento experimental foi de blocos casualizados, com quatro repetições, em esquema fatorial constituído por dois manejos da fitomassa da parte aérea (sem e com fragmentação mecânica) e seis épocas de coleta [0;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
(21 reference statements)
2
4
0
7
Order By: Relevance
“…This occurred as the amount of biomass on the ground decreased ( Figure 1A). Similar results were observed in several studies on different cover crops, such as sun hemp and millet (Costa et al 2012, Soratto et al 2012, as well as pigeonpea and pearl millet intercropping (Ferrari Neto et al 2012). Thus, the average levels of N, K, Ca, Mg and C declined by 36 %, 90 %, 29 %, 44 % and 6 %, respectively, between the first and last evaluations.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This occurred as the amount of biomass on the ground decreased ( Figure 1A). Similar results were observed in several studies on different cover crops, such as sun hemp and millet (Costa et al 2012, Soratto et al 2012, as well as pigeonpea and pearl millet intercropping (Ferrari Neto et al 2012). Thus, the average levels of N, K, Ca, Mg and C declined by 36 %, 90 %, 29 %, 44 % and 6 %, respectively, between the first and last evaluations.…”
Section: Resultssupporting
confidence: 89%
“…During the sampling periods, there was a 29 % increase in Si concentration from 0 to 68 DAM ( Figure 2H), probably due to the rise in phytolith concentration, as the biomass was degrading. Several studies have also found increased Si concentration over time in different species (Costa et al 2012, Ferrari Neto et al 2012, Soratto et al 2012.…”
Section: Resultsmentioning
confidence: 93%
“…Dessa forma, faz-se necessário introduzir plantas com potencial para produzir quantidade de matéria seca de modo que o solo permaneça coberto o maior tempo possível, para a implantação da próxima cultura (Torres et al 2008, Pacheco et al 2011). Assim, a busca por culturas alternativas, que possam deixar sobre o solo camada de palha com quantidade, qualidade e distribuição uniformes, tem se tornado o tema de diversas pesquisas (Pacheco et al 2011, Costa et al 2012, Ferrari Neto et al 2012, Nascente & Crusciol 2012. Nesses trabalhos, verifica-se algumas opções, como o milheto, apontado como uma das culturas responsáveis pela expansão do SPD, na Região Central do Brasil (Salton & Kichel 1997).…”
Section: Key-wordsunclassified
“…In the last sampling, the values of these ratios were 43, 305 and 527 for pearl millet, 32, 283 and 798 for pigeonpea and 48, 342 and 822 for the intercrop, respectively (Figure 2c,d,e). Costa et al (2012) also observed an increase in the C/N, C/P and C/S ratios, and reduction in the C/Si ratio over time in crotalaria SDM.…”
Section: Resultsmentioning
confidence: 61%
“…Costa et al (2012) reported that the C/N, C/P, C/S and C/Si ratios express the resistance of SDM to decomposition. Nevertheless, due to the scarcity of studies that relate the C/Si ratio to SDM degradation in the soil, more studies are required to establish the importance of this relation to residue persistence.…”
Section: Introductionmentioning
confidence: 99%